(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
The new injunction is no longer repression but enjoy! – echoing Kafka’s libertine father. We are lulled into the false freedom of de-sublimation, where sex is a set of techniques. The alternative? Visceral love, expressed in Sartre’s Saint Genet - and Lévinas’s notion of desire, related to a radical ethical stance.